2022
DOI: 10.30692/sisad.1093130
|View full text |Cite
|
Sign up to set email alerts
|

İkti̇sat Alaninda Göç Konusunda Yapilan Li̇sansüstü Tezleri̇n Bi̇bli̇yometri̇k Anali̇zi̇

Abstract: Öz: Uluslararası göç, bireysel bir eylem olmanın ötesinde toplumları ve gelecek kuşakları etkileyen önemli bir olgudur. Bu araştırmanın amacı, ekonomi konusunda göç alanında yapılan lisansüstü tez çalışmalarını çeşitli parametreler doğrultusunda bibliyometrik olarak incelenmesidir. Bu amaçla YÖK ulusal tez merkezi veri tabanı üzerinden 131 lisansüstü tez çalışması tespit edilmiş ve ilgili çalışmalar bibliyometrik tekniklerle analiz edilmiştir. Analizlerden elde edilen sonuçlar incelendiğinde, en çok Türkçe dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…According to Aydın & Altuntaş-Gürsoy (2022), qualitative research is almost four times more than quantitative research. However, in the studies in the fields of social work (Apak, 2018), economics (Haydaroğlu, 2022) and psychology (Kabasakal & Soylu, 2021), it was determined that most of the researches are structured with a quantitative approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Aydın & Altuntaş-Gürsoy (2022), qualitative research is almost four times more than quantitative research. However, in the studies in the fields of social work (Apak, 2018), economics (Haydaroğlu, 2022) and psychology (Kabasakal & Soylu, 2021), it was determined that most of the researches are structured with a quantitative approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the national and international literature, a study could not be found within the available resources, which analyzes the researches on the phenomenon of migration in both Turkish education and Social Studies education in a holistic and systematic way. Some of the studies are within the field of public administration/urbanism (Ağın, Zengin-Çelik & Tezan, 2021;Aksu-Kocatürk, 2021), social work (Apak, 2018), economics (Haydaroğlu, 2022), painting and music (Bastaban & Yılmaz, 2022), psychology (Kabasakal & Soylu, 2021) and focused on the research year, subject, type, design/method and department. Although researches in the field of education have been identified among the studies examining academic research on the phenomenon of migration (Avcıoğlu, 2020;Canbey-Özgüler, 2019;Coşkun, Sarıalioğlu & Dinçer, 2020), regardless of the field of science in Yerli (2018), Açıkalın & Neyişçi (2020), Alkar & Atasoy's (2020) studies, they have not been separated as Turkish and Social Studies education.…”
Section: Introductionmentioning
confidence: 99%